Tendência e fatores associados na utilização de serviços odontológicos em pré-escolares brasileiros - Agostini, Bernardo Antonio (2015)
The use of dental care services has been associated with contextual factors and time-related variations. However, there is a lack of studies assessing the association between contextual variables and the use of dental care services as well as the trends of oral health care utilization in preeschoolers. This dissertation aimed to assess the association between individual and contextual socioeconomic factors with the use of dental health services in Brazilian preschool children. As well, assess the trend in the use of dental health care, type of service and reasons for dental care utilization considering time-related variations of age, period and cohort ( Age-Period- Cohort effect ). A representative sample of 1,765 preschool children from Santa Maria-RS, Brazil, was collected from 3 oral health surveys performed in 2008, 2010 and 2013. Data from these surveys were used to assess the trend in the use of dental health services among preschool children considering the influence of Age- Period-Cohort effect. A total of 639 participants from the second period of data collection (2010) were used to assess the influence of contextual factors in the use of dental care. Contextual social determinants included the presence of worker s associations and the number of dentists in thethe neighborhood in which the child was living. Data analysis used multilevel Poisson regression models to assess the association between predictors and the outcomes in both studies. The chi-square for trends was also used to assess the the prevalence of each outcome considering time-related changes. Presence of wokers association in the neighborhood favors preschool children to use dental health services. Children who lived in a neighborhood with workers association visited the dentist 65% more than their counterparts. There is a time-related vartion (Age-Period-Cohort effect) in the useof dental health services along the years of study; age influenced straightly the dental visits prevalence, and period and cohort effects influenced significantly the type of service used and the reasons for dental seek. There is a significant association between individual and contextual social determinants and the use of dental care services in preschool children. The study also found a significant age-period-cohort effect in the use of dental care service which may be considered when planning public health strategies that facilitate dental acess for this population.